Effects of Metaverse Experience on Behavioral Intention of Visitors: Moderating Role of Similarity Between Virtual and Real Experience - Shin, Seunghun; Koo, Chulmo; Kim, Jungkeun; Gursoy, Dogan (Emerald, 2024)
Purpose: This paper aims to examine the impact of metaverse experiences on customers’ offline behavioral intentions: How do customers’ visits to a hospitality business’s virtual property in the metaverse affect their intentions to visit the physical property in the real world? Design/methodology/approach: Based on the general learning model and social cognitive theory, this research hypothesizes the positive impact of metaverse experiences on customers’ visit intentions and explores two boundary conditions for positive impact: user–avatar resemblance and servicescape similarity. Two experimental studies were conducted. Findings: Metaverse experience has a significant impact on customers’ visit intentions, and this impact is moderated by user–avatar resemblance and servicescape similarity. Research limitations/implications: This research addresses the call for empirical studies regarding the effects of metaverse experience on people’s behavioral intentions. Originality/value: As one of the earliest empirical studies on the marketing effects of the metaverse, this research provides a basis for future metaverse studies in the hospitality field.
Keywords: 35 Commerce, Management, Tourism and Services; 3503 Business Systems In Context; 3504 Commercial Services; 3506 Marketing; 3508 Tourism; Behavioral and Social Science; 1504 Commercial Services; 1505 Marketing; 1506 Tourism; Sport, Leisure & Tourism; Metaverse; General learning model; Social cognitive theory; Avatar; Servicescape